MUSE: A second-generation integral-field spectrograph for the VLT - McDermid, R; Bacon, R; Bauer, S; Boehn, P; Boudon, D; Brau-Nogue, S; Caillier, P; Capoani, L; Carollo, C; Champavert, N; Contini, T; Daguise, E; et al. (2008)
The Multi Unit Spectroscopic Explorer (MUSE) is a second-generation instrument in development for the Very Large Telescope (VLT) of the European Southern Observatory (ESO), due to begin operation in 2011/12. MUSE will be an extremely powerful integral-field spectrograph fed by a new multiple-laser adaptive optics system on the VLT. In its usual operating mode, MUSE will, in a single observation, produce a 3-dimensional data cube consisting of 90,000 R 3000 spectra, each covering a full spectral octave (480-930 nm), and fully sampling a contiguous 1×1 arcmin2 field with 0.2×0.2 arcsec2 apertures. A high-resolution mode will increase the spatial sampling to 0.025 arcsec per pixel. MUSE is built around a novel arrangement of 24 identical spectrographs (each comparable to a 1st generation VLT instrument), which are fed by a set of 24 precision image slicers. MUSE is designed for stability, with only 2 modes, and virtually no moving parts, allowing very long exposures to be accumulated. Together with high throughput, this ensures that MUSE will have extreme sensitivity for observing faint objects. We overview the technical and scientific aspects of MUSE, highlighting the key challenges for dealing with the unprecedented quantity and complexity of the data, and the integration with the VLT adaptive optics facility (AOF) - a key development on the path to extremely large telescopes (ELTs). © 2008 Springer-Verlag Berlin Heidelberg.